2007
DOI: 10.1103/physrevb.75.024401
|View full text |Cite
|
Sign up to set email alerts
|

Exact one- and two-particle excitation spectra of acute-angle helimagnets above their saturation magnetic field

Abstract: The two-magnon problem for the frustrated XXZ spin-1/2 Heisenberg Hamiltonian and external magnetic fields exceeding the saturation field B s is considered. We show that the problem can be exactly mapped onto an effective tight-binding impurity problem. It allows to obtain explicit exact expressions for the two-magnon Green's functions for arbitrary dimension and number of interactions. We apply this theory to a quasi-one dimensional helimagnet with ferromagnetic nearest neighbor J 1 < 0 and antiferromagnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
80
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 13 publications
10
80
0
Order By: Relevance
“…However, as shown by earlier studies, 4,6,10,11,12 this is not the true instability for the quantum case in the whole parameter region −4J 2 < J 1 < 0.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…However, as shown by earlier studies, 4,6,10,11,12 this is not the true instability for the quantum case in the whole parameter region −4J 2 < J 1 < 0.…”
mentioning
confidence: 84%
“…At the boundary J 1 = −4J 2 the zero-field ground state is highly degenerate such that states from vanishing magnetization to full polarization share the same energy. 9 For the parameter range −4J 2 < J 1 < 0 of our main interest, Chubukov 6 suggested that the ground state just below the saturation field should be a nematic state made up of bound magnon pairs with a commensurate total momentum k = π if −2.67J 2 < J 1 < 0 (2.67 ≈ 1/0.38) and with an incommensurate momentum k < π otherwise, which was partly verified by mean-field theory, 10 numerical study, 11 Green's function analysis which fixed the commensurate-incommensurate transition point to J 1 /J 2 = −2.66908 (= −1/0.374661), 12 and weak-coupling bosonization analysis. 4,11,13 While earlier calculations of the ground-state magnetization process suggested metamagnetic transitions, 10,14 recent densitymatrix renormalization group (DMRG) study 11 finds that the total magnetization of finite-size chains changes by ∆S z = 2 at J 1 = −J 2 , ∆S z = 3 at J 1 = −3J 2 , and ∆S z = 4 at J 1 = −3.75J 2 below saturation, implying that the magnetization curve is continuous in the thermodynamic limit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…. .. 5 Beyond the commensurate-incommensurate transition point, the total momentum k changes continuously as Fig. 7.…”
Section: Multimagnon Instabilitymentioning
confidence: 99%
“…According to Ref. 44, the field h s,2m at which the two-magnon bound-state gap closes is given by h s,2m / J 2 = ͓1+͑⌬ +1͒ 2 − ⌬ 2 ͑1−␤͒ 2 ͔ / ͓2͑1−␤⌬͔͒ while the respective value for one-magnon states is given by h s,1m / J 2 = ͑⌬ −1͒͑1+␤͒ + ͑4+␤͒ 2 / 8. Comparing those two fields, one finds, for example, that for ␤ = −0.3 the instability of the fully polarized state at the saturation field is by condensation of the two-magnon bound states at ⌬Ͼ⌬ s Ӎ 0.54, and by one-magnon states below that value.…”
Section: Magnetization Curvesmentioning
confidence: 99%